2018
DOI: 10.14744/bej.2018.32032
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of retinopathy of prematurity in a tertiary care center in Turkey

Abstract: The objective of our study was to determine the incidence of retinopathy of prematurity (ROP) in our hospital, which gives tertiary health services. Methods: In this retrospective study, the medical files of the infants, who were born before the 36th gestational age and applied for the examination of ROP between 2014 and 2017 to Istanbul Kanuni Sultan Suleyman Training and Research Hospital, were investigated. The birth weight, gestational age, type of delivery, and the development of ROP were recorded. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Ekinic et al found the incidence of ROP was 32.4% at tertiary center in Turkey. 20 This finding reflect the risk of ROP incidence at higher gestational age with the subsequent need to widen current screening criteria to include premature infant with gestational age equal or less than 34 week.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Ekinic et al found the incidence of ROP was 32.4% at tertiary center in Turkey. 20 This finding reflect the risk of ROP incidence at higher gestational age with the subsequent need to widen current screening criteria to include premature infant with gestational age equal or less than 34 week.…”
Section: Discussionmentioning
confidence: 91%
“…This result was consistent with that of Ekinci et al with sever ROP incidence of 8.8%. 20,34,35 Limitations of this study :the relatively small sample size, short duration of study and loss of follow up due to death of very low birth weight infants which had an effect on the final result.…”
Section: Discussionmentioning
confidence: 93%